Synergistic Chemical Synthesis and Self‐Assembly Lead to Three‐Dimensional b‐Oriented MFI Superstructures with Selective Adsorption and Luminescence Properties. Issue 12 (29th January 2018) - Ma, Xiaoting; Li, Guannan; Tao, Jiawei; Li, Ping; Zheng, Hongzhi; Li, Shougui; Xu, Yan
Abstract: Higher‐order organization of inorganic nanoparticles with hierarchical architectures and tailored functionality is crucial in the nanofabrication of advanced materials. Here we demonstrate that three‐dimensional b ‐oriented MFI superstructures can be organized by synergistic chemical synthesis and self‐assembly. The organization is accomplished by vapor treatment of tetrapropylammonium hydroxide (TPAOH)‐coated inorganic/bacterial cellulose scaffolds. TPA + acts to direct nucleation and to mediate crystal morphology leading to oriented assembly of MFI crystals along crystallographic b ‐axis, whereas bacterial cellulose holds the oriented assembly together forming three‐dimensional superstructures with macroporosity. Self‐supporting monoliths of the macroporous MFI show outstanding selective adsorption for para ‐xylene and high adsorption capacity for volatile organic compounds. Incorporating luminescent molecules imparts the macroporous monoliths the new property of adsorption tunable luminescence that may act as an optical sensor indicating the level of adsorption. The current work opens a novel space for rational organization of hierarchical materials with tailored architectures and multifunctionality. Abstract : Inspired by the organization of biominerals, we have developed a novel precursor scaffolding‐solid phase crystallization strategy for hierarchical self‐supporting zeolite monoliths with a three‐dimensional MFI superstructure by oriented assembly, which show outstanding selective adsorption for para ‐xylene and high‐adsorption capacity for volatile organic compounds.